Convocation / Priestly Lanting Layang ... [et al.] - Layang, Priestley Lanting; Abang Shamshudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
"Convocation" is used on college and university campuses worldwide to refer to a variety of ceremonies. "The act or process of gathering a group of people to a meeting" is a convocation. It usually refers to a formal college or university assembly. Convocation ceremonies mark the day graduates graduate from post-secondry colleges and universities. These highly ritualized events represent academic success.